Determination of protein value and water absorption in chickpea (Cicer Aiietinuml.) seeds during germination - Ay Tezcan, Aynur; Karataş, Şükrü; Kalkan, İndrani (North University Center of Baia Mare, 2023)
Protein and water absorption values were investigated in Cagatay and Gokhoyuk varieties of chickpea (Cicer arietinum) seeds after germination. The crude protein content were determined as 29.14% by dry weight in Cagatay and 26.13% in Gokhoyuk varieties respectively. Following imbibition, the amount of water absorption increased up to approximately 50% to 60% in both varieties. Crude protein content increased by 10.4% and 14.2% and carbohydrate content increased by 0.45% and 0.41% respectively for Cagatay and Gokhoyuk varieties of chickpea seeds. In addition, total viability of microorganisms, yeasts and molds were also determined after germination. Inactivation of microorganisms (including yeast and molds) to acceptable safe limits were noted, after soaking in hot water at 950 C for five minutes.
Keywords: Absorption; Chickpea; Germination; Protein; Soaking